2018
DOI: 10.1149/2.0131804jes
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes as Redox Shuttles in Dye-Sensitized Solar Cells Based on Electrodeposited ZnO: Tuning Recombination Kinetics and Conduction Band Energy

Abstract: In this work, a pathway to engineer both interfacial charge recombination kinetics and conduction band energy in dye-sensitized solar cells based on mesoporous electrodeposited ZnO is presented. Especially in solar cells employing metal complex redox shuttles such as Co(bpy) 3 [bpy = 2,2'-bipyridine] and Cu(tmby) 2 [tmby = 4,4',6,6'-tetramethyl-2,2'-bipyridine] these factors are crucial in order to obtain efficient devices. Controlling them is achieved by augmenting the liquid redox electrolyte with additives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…While the former consists of high-temperature sintered nanoparticles that involve grain boundaries along the path of conduction, electrodeposited ZnO is prepared at low temperatures and consists of crystalline columns perpendicular to the substrate, that is, in the transport direction of electrons, which we will confirm leading to considerably faster electron transport. , This finding fits to earlier observations that even as a bulk material, ZnO shows higher electron mobility than TiO 2 . Furthermore, we employ the sensitizer Y123 (Scheme b) that has shown to yield high efficiencies in combination with TiO 2 and kinetically fast redox couples. , Sensitization of ZnO with such organic dyes that employ only one cyanoacrylic or carboxylic acid anchoring group have shown to result in a stable power output and high EQE. …”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…While the former consists of high-temperature sintered nanoparticles that involve grain boundaries along the path of conduction, electrodeposited ZnO is prepared at low temperatures and consists of crystalline columns perpendicular to the substrate, that is, in the transport direction of electrons, which we will confirm leading to considerably faster electron transport. , This finding fits to earlier observations that even as a bulk material, ZnO shows higher electron mobility than TiO 2 . Furthermore, we employ the sensitizer Y123 (Scheme b) that has shown to yield high efficiencies in combination with TiO 2 and kinetically fast redox couples. , Sensitization of ZnO with such organic dyes that employ only one cyanoacrylic or carboxylic acid anchoring group have shown to result in a stable power output and high EQE. …”
Section: Introductionsupporting
confidence: 76%
“…Because both the TEMPO +/0 and the I 3 – /I – redox mediator solutions contain the same concentration of additives and the same solvent, it can be concluded that the TEMPO +/0 redox couple is responsible for this downward shift of the CB edge of ZnO. It has been observed in preliminary work that adsorbed cations induce a significant downward shift of the ZnO CB energy. ,, In TiO 2 -based DSSCs, such shifts are not observed if alkaline molecules are present in the redox electrolyte solution, such as the presently used MBI . These molecules control the amount of surface-adsorbed cations that would otherwise stabilize energy levels also in TiO 2 . , Because the surface of ZnO is alkaline by itself, the control of surface-adsorbed cations by alkaline molecules is mitigated .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to DSSCs with a TiO 2 substrate, Co and Cu coordination complexes can be used in devices with alternative n-semiconductor substrates, for example n-ZnO, as demonstrated by Ruess, et al (2018) [177]. In a DSSC with the organic dye DN2016, of the indoline type, a PEDOT-coated CE and the Cu(tmby) 2 mediator in acetonitrile, a PCE of 3.8% was obtained (U OP = 0.713 V, J SC = 7.5 mA•cm −2 ); with the Co(bpy) 3 mediator the PCE was 3.6% (U OP = 0.618 V, J SC = 9.3 mA•cm −2 ).…”
Section: Copper Mediatorsmentioning
confidence: 99%